“Silk Road Economic Belt” in the Context of Relations Between China and Russia - Xiaofen Qiu, - (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
The establishment of “Silk Road Economic Belt” in China, the task to revive the historic trade route between Europe and Asia. In the process of this project, China and Russia have a broad space for cooperation. For example, in the field of trade and economic cooperation, cross-border infrastructure development and expansion of bilateral trade and investment, deepen financial cooperation, promote high-technology cooperation in the field of education, strengthen the Sino-Russian energy cooperation, expansion of industrial and agricultural cooperation. At the same time both sides consider the Russian integration project - the Eurasian Economic Union and Chinese - “The economic belt of the new Silk Road” are not rival, but complementary structures.